Review of current enhanced gravity separation technologies and applications - Cole, J.; Dunne, Robert; Giblett, A. (2012)
This paper reviews the current status of batch and continuous enhanced gravity separators. An overview of the equipment and operating parameters will be provided as well as innovations that have been incorporated into the design over the last number of years. Laboratory test procedures to evaluated gravity performance will be discussed as well as industrial applications of the separators.